1966
DOI: 10.1007/bf02532997
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids of human serum

Abstract: Phospholipids extracted from normal human serum were fractionated into lecithin, lysolecithin, sphingomyelin, phosphatidyl ethanolamine, lysophosphatidyl ethanolamine, phosphatidyl serine, and phosphatidyl inositol. Identification of each was established by thin‐layer chromatography and infrared spectrophotometry. The content of plasmalogen was determined in both lecithin and phosphatidyl ethanolamine fractions. The composition of fatty acids and fatty aldehydes in isolated phospholipids is presented. The degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Its Rf value was found to be 0.42 in benzene. Its melting point was found to be 144-146 o C which is in agreement with the literature data 148-150 o C 10 . GC-MS analysis of compound I showed that its molecular mass is 400 with molecular formula C 28 H 48 O.…”
Section: Isolation and Characterization Of Isolated Compounds Compounsupporting
confidence: 90%
“…Its Rf value was found to be 0.42 in benzene. Its melting point was found to be 144-146 o C which is in agreement with the literature data 148-150 o C 10 . GC-MS analysis of compound I showed that its molecular mass is 400 with molecular formula C 28 H 48 O.…”
Section: Isolation and Characterization Of Isolated Compounds Compounsupporting
confidence: 90%
“…Aliquots representing about -75 mg of lipid were used for analysis of free fatty acids (Bergmann et al 1980) and aliquots representing about 20 mg muscle were used for analysis of lipid phosphorus (Dodge and Phillips 1967). Lipid phosphorus values were multiplied by 25 for estimation of phospholipids (Williams et al 1966). Aliquots of lipid solutions representing lipid from about 500 mg muscle were transferred to screw cap (Teflon-lined) culture tubes and aliquots of a known amount of 5-alphacholestane (about 200 micrograms) in hexane were added to each tube as internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid phosphorus in muscle lipid was determined by procedure of Dodge and Phillips (1967) and these values multiplied by 25 for estimation of phospholipids (Williams et al 1966). After addition of heneicosanoic acid (21:O) as internal standard and evaporation of hexane, portions of subcutaneous and muscle lipids were saponified, nonsaponifiables extracted and discarded, and free fatty acids isolated.…”
Section: Methodsmentioning
confidence: 99%